Characterization of the human Xq21.3/Yp11 homology block and conservation of organization in primates. - Sargent, C; Boucher, C; Blanco, P; Chalmers, I; Highet, L; Hall, N; Ross, N; Crow, T; Affara, N (2001)
The Xq21.3/Yp11 homology block on the human sex chromosomes represents a recent addition to the Y chromosome through a transposition event. It is believed that this transfer of material occurred after the divergence of the hominid lineage from other great apes. In this paper we investigate the structure and evolution of the block through fluorescence in situ hybridisation, contig assembly, the polymerase chain reaction, exon trapping, sequence comparison, and annotation of sequence data. The overall structure is well conserved between the human X chromosome and the Y chromosome as well as between the X chromosomes from different primates. Although the sequence data reveal a high level of nucleotide sequence identity for the human X and Y, there are regions of significant divergence, such as that around the marker DXS214. These are presumably the consequence of multiple rearrangements during evolution and are of particular importance with respect to the potential gene content in this segment of the interval.